The Impact of Covid-19 Pandemic on Students’ Learning Outcome in Higher Education - Andi Rahman (STAI Hubbulwathan Duri, 2021)
The current Covid-19 pandemic has had many effects on human life globally, including the implementation of education. This study aimed to obtain the impact of the Covid-19 pandemic on learning outcomes in higher education. The research method used is a cross-sectional study. The data were taken from the test results at the end of the lecture, observations, and interviews. The research was conducted at the University of Muhammadiyah Lampung, IPDN Jatinangor Campus, and the Ahmad Dahlan Institute of Technology and Business, with 120 students participating. The data analysis technique used the percentage technique and cross-tabulation. The study results concluded that student learning outcomes decreased in the 2020-2021 academic year compared to the 2019-2020 academic year. The decline in learning outcomes includes knowledge, skills, and psychology. This finding has implications for the understanding of education personnel regarding online teaching and learning design during the Covid-19 pandemic.